PEDAGOGICAL ASPECTS OF LOGARITHMIC AND RHYTHMTHERAPY ON THE DISORDERS OF FLUENCY AND THEMPO-RHYTHMIC ORGANIZATION OF SPEECH OR STUTTERING - B. Petrova (Trakia Journal of Sciences)
The relationship between logarithmic and rhythm therapy is multifaceted, which explains the good opportunities for their application in a primary school in students with fluency and tempo-rhythmic organization of speech, which form the picture of development- stuttering. Research related to the pedagogical aspects of this application is relevant, as the problem is analyzed mainly theoretically as related to other scientific fields. This article presents methods for corrective work, which is also the concept of this framework of speech therapy rhythmic: object, subject, goal and tasks. A theoretical analysis on the topic was made and a study of the role of logarithmic and rhythm therapy from the point of view of pedagogues in primary school was presented. Тhe results are analyzed in terms of their applicability and adequacy to the learning process and pedagogical practice.